Penanganan Sampah Berbasis Pemberdayaan Masyarakat di Kabupaten Labuhanbatu - Jonni Sitorus; Siti Masliyah Lubis; Marlina Zetri; Nobrya Husni (Badan Penelitian dan Pengembangan Provinsi Sumatera Utara, 2023)
The research aim to describe pattern of waste management and local government policies in wastemanagement. This research was analyzed qualitatively with a descriptive approach andquantitatively with a simple statistical approach (without statistical tests). The results show thatthe pattern of waste handling in Labuhanbatu Regency is transporting waste from the sourcedirectly to the landfill so that the carrying capacity and capacity of the landfill is overcapacity.Community empowerment in waste management in Labuhanbatu Regency is still very minimal,with the percentage of people who have participated in community empowerment programs andactivities carried out by the local government and other agencies per each assessment indicator asfollows: environmental health counseling (10.16%); socialization about waste management andsimilar activities (13.115%); participation of members/organizational administrators who care about waste management (6.885%); waste management training to be something economicallyvaluable (6.885%); getting the opportunity to work in waste recycling management (1.311%);getting waste management facilities (1.311%); getting business capital for waste management(1.311%); getting economic benefits from waste management (2.295%); producing severalproducts from waste recycling management (4.262%); and protection efforts from the localgovernment when there is a conflict over waste management (3.607%). Labuhanbatu Regencyalready has 2 regulations and laws related to waste management, namely: Peraturan DaerahKabupaten Labuhanbatu No. 8 Tahun 2017 tentang Pengelolaan Sampah, and Peraturan BupatiLabuhanbatu No. 48 Tahun 2021 tentang Pelimpahan Sebagian Kewenangan PengelolaanPersampahan kepada Camat di Lingkungan Pemerintah Kabupaten Labuhanbatu.Keywords: waste management, community empowerment, government policy